Transient astrocyte-like NG2 glia subpopulation emerges solely following permanent brain ischemia - Kirdajova, Denisa; Valihrach, Lukas; Valny, Martin; Kriska, Jan; Krocianova, Daniela; Benesova, Sarka; Abaffy, Pavel; Zucha, Daniel; Klassen, Ruslan; Kolenicova, Denisa; Honsa, Pavel; Kubista, Mikael; et al. (Glia, 2021)
NG2 glia display wide proliferation and differentiation potential under physiological and pathological conditions. Here, we examined these two features following different types of brain disorders such as focal cerebral ischemia (FCI), cortical stab wound (SW), and demyelination (DEMY) in 3-month-old mice, in which NG2 glia are labeled by tdTomato under the Cspg4 promoter. To compare NG2 glia expression profiles following different CNS injuries, we employed single-cell RT-qPCR and self-organizing Kohonen map analysis of tdTomato-positive cells isolated from the uninjured cortex/corpus callosum and those after specific injury. Such approach enabled us to distinguish two main cell populations (NG2 glia, oligodendrocytes), each of them comprising four distinct subpopulations. The gene expression profiling revealed that a subpopulation of NG2 glia expressing GFAP, a marker of reactive astrocytes, is only present transiently after FCI. However, following less severe injuries, namely the SW and DEMY, subpopulations mirroring different stages of oligodendrocyte maturation markedly prevail. Such injury-dependent incidence of distinct subpopulations was also confirmed by immunohistochemistry. To characterize this unique subpopulation of transient astrocyte-like NG2 glia, we used single-cell RNA-sequencing analysis and to disclose their basic membrane properties, the patch-clamp technique was employed. Overall, we have proved that astrocyte-like NG2 glia are a specific subpopulation of NG2 glia emerging transiently only following FCI. These cells, located in the postischemic glial scar, are active in the cell cycle and display a current pattern similar to that identified in cortical astrocytes. Astrocyte-like NG2 glia may represent important players in glial scar formation and repair processes, following ischemia.
Keywords: NG2 glia; stab wound; Brain Ischemia; Astrocytes; Neuroglia; neuroglie; Mice; oligodendroglie; Gliosis; glióza; astrocyty; zvířata; ischemia; demyelination; oligodendrocytes; myši; astrocytes; Oligodendroglia; ischemie mozku; Animals